2017
DOI: 10.5897/ajmr2017.8432
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and FTIR characterization of lapachol derivatives against Staphylococcus aureus

Abstract: Lapachol is a natural naphthoquinone with important activity due to its chemical and structural properties. Nine semisynthetic derivatives of this substance were tested against strains of Staphylococcus spp. to identify the antimicrobial activity of these compounds. Only β-lapachone and oxime of lapachol showed good activity against the strains studied. The minimum bactericidal concentration values ranged from 62.5 to 15.62 μg/mL. The antimicrobial activity of these substances may be related to functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The presence of naphthoquinone group with C=O bond at the wavelength range of 1655-1635 cm -1 known to has its role as scavenger of superoxide radicles (Patel et al, 2007) which may benefit in the oxidation and breakdown of organic matter in wastewater treatment. The antibacterial activity was noticed with lapachol which is a natural naphthoquinone indicating the removal of pathogens in wastewater treatment (Fernandes et al, 2017). Qian et al, (2011) reported that presence of guanidine activates the antibacterial activity against the E. coli.…”
Section: Identification Of Functional Groups In the Developed Em Form...mentioning
confidence: 99%
“…The presence of naphthoquinone group with C=O bond at the wavelength range of 1655-1635 cm -1 known to has its role as scavenger of superoxide radicles (Patel et al, 2007) which may benefit in the oxidation and breakdown of organic matter in wastewater treatment. The antibacterial activity was noticed with lapachol which is a natural naphthoquinone indicating the removal of pathogens in wastewater treatment (Fernandes et al, 2017). Qian et al, (2011) reported that presence of guanidine activates the antibacterial activity against the E. coli.…”
Section: Identification Of Functional Groups In the Developed Em Form...mentioning
confidence: 99%